Competing Reactions Limit Production of Sugars in Hydrothermal Hydrolysis of Grass Silage: An Assessment of the Effect of Temperature on Sugar Production and Parasitic Energy Demand - Lin, Richen; Deng, Chen; Rajendran, Karthik; Bose, Archishman; Kang, Xihui; Murphy, Jerry D. (Frontiers in Energy Research, 2020)
Grass represents a major renewable feedstock in temperate climate zones, but its efficient utilization is challenging in biorefineries and advanced biofuels due to its structural recalcitrance. Here hydrothermal hydrolysis (100 to 180 °C, for up to 40 min duration) was investigated to improve sugar yields from grass silage. The optimal conditions (140 °C for 20 min duration) showed the highest sugar yield of 0.29 g/g volatile solid (VS) of grass silage. Further increasing the temperature to 180 °C favored degradation of sugars (such as glucose, xylose) to by-products (such as furfural, hydroxymethylfurfural). A first-order reaction model confirmed a two-step reaction with the first step hydrolysis and the second step degradation. An energy balance calculation indicated that pre-treatment at 140 °C required an energy input of 16.5 kJ/g VS, which could be significantly reduced to 5.1 kJ/g VS through efficient heat recovery. This research assists in understanding of the hydrolysis mechanism and provides a practical solution to produce grass-based sugars for further advanced biofuel and biorefinery applications.